2018
DOI: 10.5114/ceh.2018.73370
|View full text |Cite
|
Sign up to set email alerts
|

Cannulation in patients with large periampullary diverticulum using SpyBite miniforceps

Abstract: IntroductionCannulation is difficult in patients with periampullary diverticulum (PAD). The described success rate varies from 61% to 95.4%.Material and methodsFour cases with PAD in which, despite repeated attempts, we were unable to locate the papilla and cannulate. To overcome this difficulty, we used SpyBite forceps (Boston Scientific) to pull out the papillary orifice and then perform the cannulation using a sphincterotome introduced through the same working channel.ResultsThis method reduced the time req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The use of an endoscopic clip or forceps to retract an overlying diverticular rim has been reported to be a helpful technique to expose and properly orient the ampulla. [57][58][59][60][61] One study found the attachment of a clear cap to the end of a forward-viewing endoscope helpful in revealing papillae that were difficult to find. 62 Submucosal saline injection has also been described as a method of everting the papillary opening to assist cannulation of the papillary orifice.…”
Section: Management Of Peridiverticular or Intradiverticular Papillaementioning
confidence: 99%
“…The use of an endoscopic clip or forceps to retract an overlying diverticular rim has been reported to be a helpful technique to expose and properly orient the ampulla. [57][58][59][60][61] One study found the attachment of a clear cap to the end of a forward-viewing endoscope helpful in revealing papillae that were difficult to find. 62 Submucosal saline injection has also been described as a method of everting the papillary opening to assist cannulation of the papillary orifice.…”
Section: Management Of Peridiverticular or Intradiverticular Papillaementioning
confidence: 99%
“…The variation in location of the papilla in the setting of PAD can lead to an atypical orientation or obscured location, complicating endoscopic cannulation and stone extraction using traditional techniques. Indeed, there are many case reports highlighting innovative techniques to facilitate biliary cannulation in the setting of PAD including clip placement [8], the use of small diameter forceps [9][10][11], cap-fitted forward viewing endoscopy [12], and a reverse guidewire technique [13]. Further, there is concern for both orientation and length of sphincterotomy when the typical landmarks are not present, due to the diverticulum.…”
mentioning
confidence: 99%